Secure Event-Triggered Mechanism for Networked Control Systems under Injection Cyber-Attacks - Xiao Cai; Jian Kang; Kaibo Shi (Discrete Dynamics in Nature and Society)
This study focuses on the secure stability issue of networked control systems (NCSs) under injection cyber-attacks (ICAs), which have important research value of applications for network security. Firstly, a more general Lyapunov–Krasovskii functional (LKF) is constructed based on the time-delay phenomenon in systems. Secondly, a novel boundary looped function (BLF) is developed depending on the sampling period, fully considering delay and sampling information, and the initial constraints of the criteria on the matrices are effectively relaxed. In addition, appropriate integral inequalities are used, making the obtained criteria less conservative in this paper. Then, a new event-trigger mechanism (ETM) controller under ICAs is designed to control the asymptotical stability (AS) of NCSs. Finally, a numerical experiment verifies the correctness and feasibility of the theory.